1990
DOI: 10.1128/aem.56.7.2146-2151.1990
|View full text |Cite
|
Sign up to set email alerts
|

Azoreductase activity of anaerobic bacteria isolated from human intestinal microflora

Abstract: A plate assay was developed for the detection of anaerobic bacteria that produce azoreductases. With this plate assay, 10 strains of anaerobic bacteria capable of reducing azo dyes were isolated from human feces and identified as Eubacterium hadrum (2 strains), Eubacterium spp. (2 species), Clostridium clostridiiforme, a Butyrivibrio sp., a Bacteroides sp., Clostridium paraputrificum, Clostridium nexile, and a Clostridium sp. The average rate of reduction of Direct Blue 15 dye (a dimethoxybenzidine-based dye) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
109
1
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(117 citation statements)
references
References 22 publications
0
109
1
3
Order By: Relevance
“…or Bacteroides sp.) that decolorized sulfonated azo dyes during growth on solid or liquid complex media under anaerobic conditions (RAFII et al 1990).…”
Section: Isolation and Identification Of Dye Decolorizing Bacterial Cmentioning
confidence: 99%
“…or Bacteroides sp.) that decolorized sulfonated azo dyes during growth on solid or liquid complex media under anaerobic conditions (RAFII et al 1990).…”
Section: Isolation and Identification Of Dye Decolorizing Bacterial Cmentioning
confidence: 99%
“…Azoreductase activity has been identified in several bacteria, such as Xenophilus azovorans KF46 [5], Pseudomonas luteola [6], Rhodococcus [7], Shigella dysenteriae Type I [8], Klebsiella pnumoniae RS-13 [9] and Clostridium perfringens [10]. Studies on these strains suggested that some of them require flavin compounds for azoreductase activities, and others do not [11]. Recent reports from the laboratory of Dr. Stolz showed that the addition of quinoid redox mediators to anaerobically incubated cultures of various taxonomically different bacterial species could result in significantly increased reduction rate for azo dye [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic dyes such as azo dyes, xanthene dyes and anthraquinone dyes are very toxic to living organisms (Gingell and Walker 1971 ;Meyer 1981 ;Manning et al 1985 ;Rafii et al 1990). Azo dyes are a group of compounds characterized by the presence of one or more azo groups (-N N-) in association with one or more aromatic system.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although some azo dyes are non-mutagenic, their reductive degradation products, particularly aromatic amines, are mutagenic (Chung et al 1981). Most studies on azo dye biodegradation have focused on bacteria (Horitsu et al 1977 ;Idaka et al 1980Idaka et al , 1982Brown 1981 ;Zimmermann et al 1984 ;Liu and Yang 1989, 1992Ogawa and Yatome 1990 ;Rafii et al 1990 ;So et al 1990 ;Yatome et al 1990Yatome et al , 1991Yatome et al , 1993Cao et al 1993 ;Govindaswami et al 1993 ;Rafii and Cerniglia 1993 ;Hu 1996). With the exception of the study conducted by Cao et al (1993), most studies reported that mutagenic and recalcitrant aromatic amines were produced during the reductive cleavage of azo dyes by bacteria.…”
Section: Introductionmentioning
confidence: 99%